Impacts of Covid-19 in the business of brazilian geographic indications - Silva, Hellen Vitória; Medeiros, Mirna de Lima (Journal of Sustainable Competitive Intelligence, 2022)
Purpose: This study sought to analyze the impact of the COVID-19 pandemic on the production and marketing of Brazilian products and services with geographical indications. Methodology/Approach: Were used the literature review and a questionnaire sent to the 78 associations responsible for the registration of geographical indications (GIs) existing in the country until May 4, 2021, about the perceived pandemic repercussions. Originality/Relevance: The research links the distinctive sign of geographical indications directly to their producing companies, and investigates the challenges and opportunities generated by the new coronavirus in this context. Key findings: It was found that GIs were often benefited externally to the delimited area, while locally the scenario was not so advantageous. This may be due to the fact that there was more dissemination/appreciation of the topic among external clients, since geographical indications with disarticulated management and distant from local players were identified, which mayhave been aggravated in the current scenario. Theoretical/methodological contributions: It benefits both the market, by pointing out the GIs and the resilience strategies applied by them during the pandemic, and the academia, by dealing with a subject that is not widespread. Moreover, it contributes to the dissemination of knowledge regarding distinctive signs beyond trademarks and patents, which are more usual in business discussions.